The Dilemma of Happiness with Spinoza - Shahada, Mohammad; Abed AlAbraham, Abed ALrahman (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The Idea of Happiness is considered one of the most important subjects , that Spinoza had discussed, in the ethical side of his Philosophy, but his discussion came in a way superior to other philosophers, as it is said. His philosophical doctrine has been arranged by him in a mathematical way, that,s he sets up from axioms to reach the ethical proof, which gives any ethical axioms the virual value in itself.